The impact of digitalisation in scientific research: risks, opportunities and ethical challenges - De Angelis , Maria Chiara (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Internet of Things, robotics, biometrics, persuasive technology, Big Data, virtual, augmented reality, and digital platforms are pervading the world of scientific research, influencing how everyday scientific work practices are organized and conducted. In this emergent context, the essay wants to offer a theoretical reflection on the purposes and functions of digital technology in scientific research processes, enhancing the dimension of ethical choice and crucial judgment in governance processes and researchers’ professional development.